Distribution and habitat use of caribou, rangifer tarandus caribou, and moose, alces alces andersoni, in the Spatsizi Plateau Wilderness area, British Columbia - Boonstra, Rudy; Sinclair, A. R. E. (The Ottawa Field-Naturalists' Club, 1984)
A systematic aerial survey technique with calibrated transects to measure habitat preferences and movements of large mammals in remote areas of Canada is described. Four surveys were conducted in the Spatsizi Park, British Columbia, to monitor major movement patterns, distribution, and habitat preferences of caribou and moose. There was a major movement of caribou toward the northwest in winter, so that most of them were wintering along the lower portion of the Stikine River Valley, whereas in spring, movements were toward the southeast portion of the park. Caribou showed no habitat preference in late winter, a preference for burns, brush, and spruce-pine forest in spring, and a preference for alpine areas in fall. Moose tended to be restricted to the major river valleys in winter and were more widely distributed in spring and fall. Moose showed a general preference for burns or brush in all periods, with some associated preference for spruce, spruce-pine, or pine forests. In both fall and late winter, Moose showed alt avoidance of alpine habitat.